Effects of a kappa opioid receptor antagonist on delayed postoperative pain recovery in a novel mouse sleep disorder model - Ito, Hisakatsu; Kawakami, Masaaki; Yoshida, Masashi; Sugimoto, Sadamu; Takazawa, Tomonori (Frontiers in Pain Research, 2025)
IntroductionSleep disturbances have been shown to exacerbate pain sensitivity and prolong recovery from pain. However, conventional animal models of sleep disturbance, which involve physical disruptions, such as water or forced movement, might not fully represent modern human sleep disorders.MethodsWe utilized a novel sleep disorder model, the perpetual avoidance of water on a wheel (PAWW) model, which induces spontaneous activity, chronic stress, and abnormal sleep–wake cycles in mice. We investigated the effects of a kappa opioid receptor (KOR) antagonist, nor-binaltorphimine (nor-BNI), on pain recovery in a postoperative pain model in mice in a state of disordered sleep. After 1 week of acclimation, the mice were housed in PAWW or regular cages for 2 weeks. Sleep conditions were evaluated using electroencephalogram and electromyogram recordings, and postoperative pain recovery following plantar incision was assessed using von Frey tests. We also examined the effects of nor-BNI on pain recovery.ResultsThe evaluation showed that PAWW housing significantly increased activity during the light phase, disrupted sleep patterns, and delayed postoperative pain recovery. The administration of nor-BNI alleviated the delayed pain recovery.DiscussionThese findings suggest that sleep disorders, such as those modeled by PAWW, could delay postoperative pain recovery, and that KOR antagonists might provide therapeutic benefits in the management of delayed recovery of postoperative pain induced by sleep disorders.